Penerapan Metode PROMETHEE dalam Sistem Penunjang Keputusan untuk Pemilihan Supplier di ZIO Petshop & Petcare - Alfan Subkhi; Asep Erlan Maulana; Ichsan Ramadhani (JiTEKH, 2025)
Strategic supplier selection plays a pivotal role in maintaining the operational stability and competitiveness of & Petcare. Currently, the primary challenge lies in the reliance on a manual, intuition based selection process, which is prone to subjectivity and inefficiency in decision making. This study aims to design and build a web based Decision Support System (DSS) by implementing the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) to generate objective supplier recommendations. The system development methodology adopts the Waterfall model, encompassing analysis, design, implementation, and testing phases. In this case study, the system evaluates ten supplier alternatives based on five fundamental criteria: product quality, service, distance, price, and delivery time. The computational results demonstrate that the PROMETHEE method effectively provides accurate rankings, with Supplier 5 achieving the top position with the highest Net Flow value of 0.6222. Validation through Black Box and White Box testing confirms that all system functionalities and logic structures operate correctly and efficiently. The implementation of this system proves effective in enhancing accuracy, objectivity, and time efficiency in the supplier selection process.